DIRECTIONS FOR IMPROVING THE ENTERPRISE MANAGEMENT PROCESS IN THE CONTEXT OF DIGITALIZATION - I. Naydenko; T. Yoienko (Вестник Северо-Кавказского федерального университета)
The digital transformation of the economy is a global trend in the competitiveness of Russian manufacturing enterprises, in connection with which the opportunities for enterprises to improve their efficiency are expanding. In the region considered in the article - the Rostov region, among the main sectors of the economy, industry takes the leading place. In this article, the authors present the results of a study of the digital transformation of industrial enterprises in the Rostov region. The study analyzes digital solutions that are being implemented at manufacturing enterprises, as well as factors slowing down the development of digitalization in the industrial sector of the economy. The analysis of the development of the largest industrial enterprises in the region in the context of the implementation of digital solutions into their activities was carried out and on this basis a set of indicators of their digital transformation was developed, as well as a method for assessing the digital potential of industrial structures was proposed.